2022
DOI: 10.3390/ijms24010546
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leptin as a Link between Asthma and Obesity: A Systematic Review and Meta-Analysis

Abstract: Asthma and obesity are considered as highly prevalent diseases with a great impact on public health. Obesity has been demonstrated to be an aggravating factor in the pathogenesis of asthma. Adipose tissue secretes proinflammatory cytokines and mediators, including leptin, which may promote the development and severity of asthma in obese patients. This study is a systematic review and a meta-analysis based on the relationship between leptin and asthma during obesity. MEDLINE, Cochrane, EMBASE and CINAHL databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Prior studies have shown increased serum leptin levels in asthma patients compared to controls. A Meta‐analysis by Sánchez‐Ortega et al demonstrated through 15 studies that patients with asthma and obesity had elevated levels of leptin 9 . Consequently, research has focused on investigating the potential connection between systemic leptin levels and CRS 62‐64 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have shown increased serum leptin levels in asthma patients compared to controls. A Meta‐analysis by Sánchez‐Ortega et al demonstrated through 15 studies that patients with asthma and obesity had elevated levels of leptin 9 . Consequently, research has focused on investigating the potential connection between systemic leptin levels and CRS 62‐64 .…”
Section: Discussionmentioning
confidence: 99%
“…A Meta-analysis by Sánchez-Ortega et al demonstrated through 15 studies that patients with asthma and obesity had elevated levels of leptin. 9 Consequently, research has focused on investigating the potential connection between systemic leptin levels and CRS. [62][63][64] In our Meta-analysis of 2 published studies, we reported that the mean serum leptin level in patients with CRSwNP was over 2-times greater compared to healthy controls independent of BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent meta-analysis by Sánchez-Ortega et al [38], substantial evidence supports Leptin's role as a mediator in asthma development and severity. This may be because of its functional similarities with IL-6, a well known pro-inflammatory cytokine associated with asthma, and its impact on the survival and proliferation of ILC2 and Th2 cells, which are key cell types in T2-high asthma.…”
Section: Metabolic Inflammationmentioning
confidence: 97%